The Role of Electives in BAMS Education: A Close-Ended Observational Survey Study - Saraswati, Vibha; Abdilahi, Abdiwahab (Journal of Educational Research and Policies, 2025)
Elective is an online program introduced in B.A.M.S./ B.U.M.S/ B.S.M.S/ B.S.R.M.S curriculum to provide an opportunity to the students of Ayurveda, Unani Siddha & Sowa - Rigpa to get introduced, exposed and oriented to various allied subjects that are required to understand and build an inter - disciplinary approach. By offering elective subjects, institutions can cater to the diverse interests and career aspirations of BAMS students, fostering a well - rounded and adaptable workforce. This paper delineates the rationale behind incorporating electives, emphasizing the potential for enhancing student engagement, promoting interdisciplinary learning, and nurturing innovation within Ayurvedic practice. Additionally, it explores the process of selecting and designing elective courses, considering factors such as industry demand, faculty expertise, and student preferences. Furthermore, the article discusses the anticipated challenges and opportunities associated with implementing elective modules, including resource allocation, curriculum coherence, and assessment methods. Through the integration of elective courses, the BAMS curriculum can evolve to meet the evolving needs of the healthcare landscape while empowering students to pursue their individual passions and professional goals. Aim of this article is to investigate the significance of elective courses into the Bachelor of Ayurvedic Medicine and Surgery (BAMS) curriculum, heralding a new era of flexibility and specialization in Ayurvedic education on the basis of a survey study.